СТРУКТУРНЫЕ СДВИГИ В КАЗАХСТАНЕ В УСЛОВИЯХ ФОРМИРОВАНИЯ НАУКОЕМКОЙ ЭКОНОМИКИ [1] - A. A. Satybaldin; F. G. Alzhanova; A. K. Amrin; Zh. .. Dusebaeva (Экономика: стратегия и практика, 2018)
The purpose of this study is to examine the dynamics and intensity of structural shifts in GDP and employment in Kazakhstan and, based on the results of the assessment, to identify sectors of the economy that form employment potential in the long term. The analysis showed that the industry as a whole, and the manufacturing industry in particular, show reduced structural dynamics and that the potential for employment growth in this sphere is limited as well. The analysis revealed a trend of accelerated growth in employment in the services sector as compared to global dynamics and the dynamics that is being formed in countries with an average level of development. This led to the conclusion that in Kazakhstan, the main employment potential is being formed in the services sector for the future.It is recommended, taking into account general trends in the expansion of the service sector in the world and Kazakhstan as well as the conditions and prospects for industrial development in Kazakhstan, special attention should be paid to the sector of knowledge of intensive services. The growth of this sector is critically linked to the quality of human capital, the development of knowledge creation and dissemination systems, which in turn is an important prerequisite for adaptation to conditions of the Industry 4.0.